Hubungan Antara Konformitas Dengan Gaya Hidup Hedonisme - Fitriyani, Nabila Nur; , Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2016)
The hedonism lifestyle is the pattern of life of someone who always looked about pleasure, happiness and enjoyment as a primary goal. One of the factors that influence is the conformity of the group. This research aims to know the relationship between the conformity with the lifestyles of hedonism, the level of conformity, the level of hedonism lifestyle and how much influence conformity with the lifestyles of hedonism.This research using quantitative methods. The subject of the research used in this study are students of vocational secondary school XI (CMS) totalling 90 students.The results obtained correlation coefficients r of 0.063 and sig = 0.276; p> 0.05, which showed that there was no connection between the conformity with the lifestyles of hedonism. The effective contribution of the conformity of 0.39% against the hedonism lifestyle.